2007
DOI: 10.1590/s0037-86822007000400022
|View full text |Cite
|
Sign up to set email alerts
|

Vírus rábico em morcego Nyctinomops laticaudatus na Cidade do Rio de Janeiro, RJ: isolamento, titulação e epidemiologia

Abstract: The first case report of rabies in bats of the species Nyctinomops laticaudatus, in the city of Rio de Janeiro City, is presented. Virus isolation and titration were performed in different tissues, and high titers were found in the brain and salivary glands. Rabies occurrence in such an infrequent species in this state suggests that the disease may be more prevalent than it appears to be.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
1
4
0
2
Order By: Relevance
“…A large number of positive bats and also rabid stray dogs and cats are found in many places around the City, and could be unnoticed because of underreporting. These observations are in agreement with those of Silva et al 9 . Despite this not being the focus of this study, the necessity for the effective control of stray animals in the urban environment is evident.…”
Section: Acknowledgmentssupporting
confidence: 94%
See 1 more Smart Citation
“…A large number of positive bats and also rabid stray dogs and cats are found in many places around the City, and could be unnoticed because of underreporting. These observations are in agreement with those of Silva et al 9 . Despite this not being the focus of this study, the necessity for the effective control of stray animals in the urban environment is evident.…”
Section: Acknowledgmentssupporting
confidence: 94%
“…In the City of Rio de Janeiro, a larger study with more samples is required in order to reveal the true prevalence of rabies in non-hematophagous bats. Except for the report of Silva et al 9 , similar studies are lacking in the city and even in the State of Rio de Janeiro. Thus, this paper seeks to contribute to a better understanding of this disease in the city, and to encourage the implementation of health education programs and investment in monitoring systems of these reservoirs in order to increase the number of animals sent for diagnosis.…”
Section: Discussionmentioning
confidence: 91%
“…In urban areas, this virus has been isolated mainly from insectivorous and frugivorous bats [8][9][10][11][12] . However, up to now, no human rabies cases have been registered in Brazil resulting from aggression by these bats involving viral variants related to these species.…”
Section: Molossus Molossusmentioning
confidence: 99%
“…It is highly likely that these results are underestimated due to the limited number of published reports concerning positive bats in these regions of the country. Among the few papers 11,14,17,20,21,25,43,52,62,66,67,70,78,79,81,82 reporting the sex of rabies positive bats, 47 were female: 13 belonging to Molossidae, 23 to Vespertilionidae and 11 A. lituratus of the Phyllostomidae family; 43 were male belonging to Molossidae (13), Vespertilionidae (14) and Phyllostomidae (16). CUNHA et al (2006) 21 reported 68 positive bats, 33 females and 35 males, but species were not shown.…”
mentioning
confidence: 99%
“…Regarding bat age, reports are also scarce 20,21,25,43,66,67,70,78,82 . The majority were adults (88%) belonging to Molossidae (7), Vespertilionidae (7) and Phyllostomidae (8).…”
mentioning
confidence: 99%